Motivations and consequences of using the feminist escrache as a mechanism of public denunciation by victims of sexual violence in Colombia, a critical analysis of the patriarchal penal system (2022)
In this text, under a critical feminist approach and incorporating a distributive analysis of law, I made a qualitative analysis of 5 cases, in which I studied the decision of women victims of sexual violence in Colombia to resort to feminist public denunciation as an alternative complaint mechanism. In the research I highlight the role of de facto and de jure impunity faced by women victims of sexual violence in the Colombian patriarchal criminal system, demonstrating the complex relationship between criminal law and women. Furthermore, I show how, by making use of such an alternative mechanism in a patriarchal society, women are exposed to re-victimizing legal and social sanctions. In this context, I propose that the feminist public denunciation is a tool for change to make visible the shortcomings and deficiencies of the patriarchal penal system, to try to reform it by including our voices, needs and interests.